Complex oxides
A composite oxide with a perovskite structure addresses the conductivity and reaction rate limitations of conventional IT-SOFC cathode materials, enhancing performance through optimized metal element ratios and structure, thereby improving energy conversion efficiency.
Patent Information
- Application Number
- JP2020217739
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-25
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2040-12-25
AI Technical Summary
Conventional cathode materials for IT-SOFCs exhibit unsatisfactory electronic conductivity, oxide ion conductivity, and oxygen surface exchange reaction rates, limiting their practical application.
A composite oxide with a perovskite structure, represented by AxB1-yOz, where A is a divalent metal, B is a trivalent or tetravalent metal, and C is a divalent, trivalent, or tetravalent metal, with specific stoichiometric ratios, enhancing electron conductivity, oxide ion conductivity, and oxygen surface exchange reaction rates.
The composite oxide demonstrates high values in electronic conductivity, oxide ion conductivity, and oxygen surface exchange reaction rates, promoting cathode reactions and improving energy conversion efficiency in IT-SOFCs.
Smart Images

Figure 0007611696000008 
Figure 0007611696000009 
Figure 0007611696000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite oxide of multiple metals. The composite oxide of the present invention is particularly suitable for use in various electrochemical elements that utilize oxide ion conductivity. [Background technology]
[0002] A solid oxide fuel cell (SOFC) is a fuel cell that uses solid ceramics with oxide ion conductivity as an electrolyte. SOFCs have high energy conversion efficiency and high power density. Because SOFCs operate at high temperatures, they have the advantage of not requiring expensive precious metal catalysts, which are required for other types of fuel cells. SOFCs also have the advantage of being able to directly use not only hydrogen but also hydrocarbons as fuel, since they are capable of internal reforming of fuel. Furthermore, because SOFCs can recover and use waste heat, they can achieve high energy conversion efficiency.
[0003] Although SOFCs have the various advantages mentioned above, they have traditionally been criticized for their shortcomings, such as rapid thermal degradation, malfunctions due to thermal shock, and long start-up times, all of which are caused by their high temperature operation. In response to this, the development of IT-SOFCs, which can operate at lower temperatures than conventional ones, is underway. However, in IT-SOFCs, the performance of each single cell decreases due to the low operating temperature. This is due to an increase in the internal resistance, including the electrodes of the single cell. In other words, the decrease in operating temperature causes a significant increase in the cathode reaction resistance, which is the cause of the decrease in single cell performance. Therefore, the promotion of the cathode reaction has become an issue in order to reduce the internal resistance of IT-SOFCs and increase their energy conversion efficiency.
[0004] One method for promoting the cathode reaction of SOFCs is to use a mixed conductor capable of conducting both oxide ions and electrons, i.e., an n-type mixed conductor, as the cathode. A conventional technique for such mixed conductors is known, for example, from Non-Patent Document 1. In this document, Ba, which is an n-type mixed conductor, is used. 1-y Ndy In 1-x Mn x O 3-δ has been proposed. This material is a Ba-In composite oxide co-doped with Nd and Mn, and has a perovskite structure. This material has a negative Seebeck coefficient and exhibits oxide ion conductivity. In other words, it is an n-type mixed conductor. [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] Chem. Mater. 2019, 31, 2713-2722 Summary of the Invention [Problem to be solved by the invention]
[0006] The material described in Non-Patent Document 1 has a certain degree of electronic conductivity and oxide ion conductivity. However, the level of conductivity is still not sufficient for use as a cathode material in SOFCs and is not suitable for practical use. In addition, the oxygen surface exchange reaction rate is not satisfactory. Therefore, an object of the present invention is to provide a composite oxide which exhibits high values for all of electronic conductivity, oxide ion conductivity, and oxygen surface exchange reaction rate. [Means for solving the problem]
[0007] The present invention provides a composite oxide having a perovskite structure, which is represented by the following formula (1). A x B y C 1.00-y O z (1) In formula (1), A represents one or more divalent metal elements, B represents one or more metal elements having an average valence of 3 to 4, C represents one or more metal elements having an average valence of 2 to 4 other than B; x is a number between 0.95 and 1.05. y is a number between 0.65 and 0.95, z represents a number between 2.3 and 3.1. Effect of the Invention
[0008] According to the present invention, there is provided a composite oxide which exhibits high values for all of electronic conductivity, oxide ion conductivity, and oxygen surface exchange reaction rate. [Brief description of the drawings]
[0009] [Figure 1] 1 is a graph showing the results of X-ray diffraction measurement of the composite oxides obtained in the respective examples. [Diagram 2] 1 is a graph showing the temperature dependence of the Seebeck coefficient of the composite oxide obtained in each example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described below based on its preferred embodiments. The present invention relates to a complex oxide. The complex oxide of the present invention is represented by the following formula (1). A x B y C 1.00-y O z (1) In formula (1), A, B, and C each represent a different metal element. Therefore, the composite oxide of the present invention contains at least three different metal elements. In the present invention, by appropriately selecting the metal elements A, B, and C and appropriately controlling the content ratio of each metal element, it is possible to obtain a composite oxide having a perovskite structure that exhibits higher values of electronic conductivity, oxide ion conductivity, and oxygen surface exchange reaction rate than conventional ones.
[0011] A divalent element is used as the metal element represented by A in formula (1) (hereinafter, for convenience, also referred to as "A element"). The A element can be used alone or in combination of two or more kinds.
[0012] As described above, the A element has a divalent valence. In particular, when the A element has only a divalent valence, a complex oxide having a perovskite structure and having electronic conductivity and oxide ion conductivity can be easily synthesized. From this viewpoint, the A element is preferably a Group 2 element. Among the Group 2 elements, it is preferable to use one or more elements selected from the group consisting of Ca, Sr, and Ba, from the viewpoint of more easily obtaining a complex oxide having electronic conductivity and oxide ion conductivity, and Ca is particularly preferably used.
[0013] In the composite oxide of the present invention, when the content of the A element is adjusted so that x in formula (1) is a number in the range of 0.95 to 1.05, a composite oxide having a perovskite structure with electronic conductivity and oxide ion conductivity can be easily synthesized. From this viewpoint, the value of x is preferably 0.97 to 1.03, more preferably 0.99 to 1.01.
[0014] The metal element represented by B in formula (1) (hereinafter, for convenience, also referred to as "element B") is an element having an average atomic valence of 3 to 4. The element B can be used alone or in combination of two or more.
[0015] "The average valence is 3 or more and 4 or less" means that the valence of the B element contained in the composite oxide of the present invention is 3 or 4, or the valence of the B element is not uniquely determined, and the B element exists in the composite oxide in a state of multiple valences, and the average valence is 3 or more and 4 or less. This average valence is represented by Σ(Vi×Mi / 100). In the formula, Vi represents the valence, and Mi represents the atomic ratio (at%) of the B element whose valence is Vi.
[0016] When the composite oxide of the present invention contains two or more kinds of B elements or when B elements are present in a multi-valence state in the composite oxide, the average valence of B elements is represented by Σ(Vi×Mi / 100), where Vi represents the valence of B elements and Mi represents the atomic ratio (at%) of all B elements having a valence of Vi.
[0017] From the viewpoint of more easily synthesizing a composite oxide having a perovskite structure having electronic conductivity and oxide ion conductivity, and from the viewpoint of exhibiting high electronic conductivity and high oxide ion conductivity, the average valence of the B element is preferably 3.2 to 4.0, and more preferably 3.3 to 3.9.
[0018] The B element may have two or more valences. Since the B element has an average valence of 3 to 4, it is easy to synthesize a complex oxide having a perovskite structure with high electronic conductivity and oxide ion conductivity. From this viewpoint, it is preferable to use a transition metal element as the B element. In particular, it is preferable to use a 3d transition metal element among the transition metal elements. As the 3d transition metal element, it is preferable to use one or more elements selected from the group consisting of Mn, Sc, and Ti, and it is particularly preferable to use Mn.
[0019] The atomic valence of the B element contained in the composite oxide of the present invention can generally be measured using instrumental analysis such as X-ray fluorescence analysis (XRF), X-ray photoelectron spectroscopy (ESCA), X-ray absorption fine structure analysis (XAFS), electron energy loss spectroscopy (EELS), and soft X-ray emission spectroscopy (SXES), or a titration method.
[0020] In the composite oxide of the present invention, the content ratio of the B element is adjusted so that y represented by formula (1) is a number in the range of 0.65 to 0.95. This range is set from the viewpoint of easily synthesizing a composite oxide having a perovskite structure with electronic conductivity and oxide ion conductivity, and from the viewpoint of expressing high electronic conductivity and high oxide ion conductivity. From this viewpoint, the value of y is preferably 0.70 to 0.90, more preferably 0.75 to 0.85.
[0021] The metal element represented by C in formula (1) (hereinafter, for convenience, also referred to as "C element") is an element having an average atomic valence of 2 to 4. The C element is a metal element other than the B element. The C element can be used alone or in combination of two or more kinds.
[0022] When the composite oxide of the present invention contains two or more kinds of C elements or when the C element is present in the composite oxide in a state of multiple valences, the average valence of the C element is represented by Σ(Vi×Mi / 100). In the formula, Vi represents the valence of the C element, and Mi represents the atomic ratio (at%) of all C elements whose valence is Vi. From the viewpoint of maintaining high electronic conductivity and high oxide ion conductivity and exhibiting a high oxygen exchange reaction rate, the average valence of the C element is preferably 2.4 to 3.4, more preferably 2.6 to 3.2.
[0023] As described above, the C element has an average valence of 2 to 4. As long as the average valence is within this range, the C element can have any valence. For example, the C element may have only one of valences of 2, 3, or 4. The C element may have two or more valences. In particular, the C element has at least one of valences of 2, 3, or 4, so that high electronic conductivity and high oxide ion conductivity are maintained and a high oxygen exchange reaction rate is obtained. From this viewpoint, it is preferable to use a transition metal element as the C element. In particular, it is preferable to use a 3d transition metal element among the transition metal elements. As the 3d transition metal element, it is preferable to use one or more elements selected from the group consisting of Co, Ni, Cu, and Fe, which are elements other than the above-mentioned B element, and it is particularly preferable to use Co.
[0024] In the composite oxide of the present invention, the content of C element is represented by (1-y) in formula (1), and by adjusting this y to a number in the range of 0.65 to 0.95, it is possible to obtain a composite oxide having a perovskite structure that exhibits high values for all of electronic conductivity, oxide ion conductivity, and oxygen surface exchange reaction rate. From this viewpoint, the value of y is preferably 0.70 to 0.90, and more preferably 0.75 to 0.85.
[0025] By adjusting the ratio of oxygen contained in the complex oxide of the present invention so that z, represented by formula (1), is a number in the range of 2.3 to 3.1, it becomes possible to develop electronic conductivity and oxide ion conductivity and to maintain the perovskite structure. From this viewpoint, the value of z is preferably 2.4 to 2.95, more preferably 2.5 to 2.9. In particular, it is preferable that the value of z is adjusted to a number such that the complex oxide of the present invention is in an oxygen-deficient state.
[0026] The values of x and y in formula (1) can be measured by ICP atomic emission spectrometry, and the value of z can be measured by iodometry or the like.
[0027] Among the composite oxides represented by formula (1), Ca x Mn y Co 1.00-y O z , Sr x Mn y Co 1.00-y O z These composite oxides have high electronic conductivity and high oxide ion conductivity. In formula (1), some deviation in composition and the presence of impurities are permitted as long as the effects of the present invention are not impaired.
[0028] The complex oxide of the present invention must have a perovskite crystal structure in order to exhibit high electron conductivity and high oxide ion conductivity. From this viewpoint, the complex oxide of the present invention preferably has a structure in which a part of the sites of element B in a complex oxide having a perovskite structure represented by formula (2): ABO3 is substituted with element C and oxygen deficiency is generated. Perovskite structures include those having unit cells of cubic, orthorhombic, tetragonal, etc. In order to make the composite oxide of the present invention have any of these unit cells, for example, it is sufficient to appropriately select a combination of element A, element B, and element C, or to appropriately select the content ratios of these elements. Whether or not the composite oxide of the present invention has any one of the crystal structures can be determined by X-ray diffraction measurement.
[0029] As described above, the composite oxide of the present invention is preferably a composite oxide having a perovskite structure represented by ABO3, in which a part of the sites of the B element is substituted with the C element. Therefore, the lattice constant of the composite oxide of the present invention varies depending on the type of the C element and its substitution amount. In addition, the lattice volume is preferably 207 Å. 3 More than 210Å 3 It was found that by setting the range as follows, it is possible to synthesize a composite oxide that exhibits high values for electronic conductivity, oxide ion conductivity, and oxygen surface exchange reaction rate. 3 More than 209.0Å3 More preferably, it is 208.2 Å or less. 3 More than 208.8 Å 3 It is even more preferable that: The lattice volume is calculated from the type of unit cell and its lattice constant determined by subjecting the composite oxide of the present invention to X-ray diffraction measurement.
[0030] The composite oxide of the present invention exhibits the properties of an n-type mixed conductor under the environment in which it is used. As a result, when the composite oxide is used as an electrode of an electrochemical element such as a solid oxide fuel cell, the redox reaction between oxygen molecules and oxide ions is easily promoted. An n-type mixed conductor is a conductor that uses electrons and oxide ions as charge carriers. In other words, it is a conductor that has electronic conductivity and oxide ion conductivity. In contrast, a p-type mixed conductor is also known. A p-type mixed conductor is a conductor that has hole conductivity and oxide ion conductivity. It is generally believed that p-type mixed conductors have a low Fermi level and a low density of electrons that contribute to the redox reaction between oxygen molecules and oxide ions. In contrast, n-type mixed conductors generally have a low energy from the Fermi level to the conduction band and a large number of activated electrons that contribute to the redox reaction between oxygen molecules and oxide ions. As a result, it is believed that the use of n-type mixed conductors as electrodes for electrochemical elements will further promote the redox reaction between oxygen molecules and oxide ions.
[0031] The temperature at which the complex oxide of the present invention is used may be selected from a wide range of temperatures as long as the complex oxide exhibits electronic conductivity and oxide ion conductivity. Whether a certain substance has the properties of an n-type conductor or a p-type semiconductor can be determined by the Seebeck coefficient of the substance. A substance with a negative Seebeck coefficient has the properties of an n-type conductor, and conversely, a substance with a positive Seebeck coefficient has the properties of a p-type semiconductor. The complex oxide of the present invention is advantageous when used as an electrode of an electrochemical element, preferably having a negative Seebeck coefficient at temperatures of 900°C or less, more preferably 700°C or less, and even more preferably 500°C or less. There is no particular limit to the lower limit of the temperature at which the Seebeck coefficient is negative, and the lower the better, but if the complex oxide of the present invention exhibits a negative value even at a temperature of about 300°C, the complex oxide of the present invention can be effectively used as an electrode of an electrochemical element that operates at a lower temperature. From the above viewpoint, it is preferable that the complex oxide of the present invention has a negative Seebeck coefficient at temperatures of 300°C to 900°C.
[0032] As described above, the composite oxide of the present invention has electronic conductivity and oxide ion conductivity. In the composite oxide of the present invention, the total electrical conductivity, which is the sum of the electronic conductivity and the oxide ion conductivity, is preferably 5.0 S / cm or more at 800° C., more preferably 8.0 S / cm or more, and even more preferably 10.0 S / cm or more. There is no particular upper limit to the value of the total electrical conductivity, but it is typically 1000 S / cm. The method for measuring the total electrical conductivity will be described in the examples below.
[0033] In the composite oxide of the present invention, the oxide ion conductivity is 5.0×10 -4 S / cm or more is preferable, and 8.0×10 -4 More preferably, the thickness is 1.0×10 S / cm or more. -3 It is more preferable that the oxide ion conductivity is 1.0×10 S / cm or more. There is no particular upper limit to the oxide ion conductivity value, but it is typically 1.0×10 -1 The oxide ion conductivity is expressed in S / cm. The method for measuring the oxide ion conductivity will be explained in the examples described later.
[0034] In the composite oxide of the present invention, it is believed that an oxygen exchange reaction takes place in an oxygen-containing atmosphere, as shown in the following formula (3), which is based on the Kröger-Bink notation.
[0035] [ka]
[0036] In electrochemical elements that utilize oxide ion conductivity, the above formula (3) is considered to be the rate-determining step. Therefore, in the composite oxide of the present invention, it is advantageous to increase the rate of the reaction represented by formula (3). The rate of the reaction represented by formula (3) is related to the oxygen surface exchange reaction rate described below, and it is known that the faster the oxygen surface exchange reaction rate is, the faster the reaction rate of formula (3) tends to be. In the composite oxide of the present invention, the oxygen surface exchange reaction rate at 600°C is 1.0 x 10 -5 mol / m 2 / s or more is preferable, and 9.0×10 -5 mol / m 2 / s or more, and more preferably 1.5×10 -4 mol / m 2 / s or more is more preferable. There is no particular upper limit, but it is typically 1.0 × 10 -2 mol / m 2 The method for measuring the oxygen surface exchange reaction rate will be described in detail in the Examples below.
[0037] Next, a preferred method for producing the composite oxide of the present invention will be described. The composite oxide of the present invention is produced by mixing the A element source, the B element source, and the C element source in a predetermined ratio and firing the mixture. Examples of the element sources include salts, oxides, and hydroxides of the respective elements. It is particularly preferable to use salts of the respective elements, and it is particularly preferable to use nitrates, since the respective element sources can be uniformly dispersed and mixed, and a composite oxide in which the perovskite structure is the main phase can be easily obtained.
[0038] When nitrates are used as the source of each element, it is preferable to employ the Pechini method, since this allows precise control of the amount of each element added and enables successful production of the desired composite oxide. In the Pechini method, nitrates and polycarboxylic acids, which are the sources of each element, are dissolved in water and mixed to generate chelate compounds of ions of A, B, and C elements and polycarboxylic acids in an aqueous solution. At the same time, a precursor is generated by an esterification reaction between the chelate compounds and a polyhydric alcohol. As the polycarboxylic acid, for example, malic acid or citric acid can be used. As the polyhydric alcohol, for example, ethylene glycol or propylene glycol can be used. The ratio of the metal element, polycarboxylic acid, and polyhydric alcohol to be added is preferably 1.5 mol or more and 9 mol or less of the polycarboxylic acid and preferably 1.5 mol or more and 9 mol or less of the polyhydric alcohol relative to the total amount of metal ions contained in the aqueous solution. In order to generate the precursor by esterification reaction, the solution is heated to a predetermined temperature, for example, 80°C or more and 180°C or less.
[0039] Next, the solution is heated to evaporate to dryness to obtain a solid. In the evaporation to dryness, it is preferable to adjust the heating temperature to remove moisture and nitrogen and to carbonize the polycarboxylic acid. For this purpose, the evaporation to dryness temperature is preferably 200°C or higher and 500°C or lower, more preferably 220°C or higher and 450°C or lower, and even more preferably 250°C or higher and 400°C or lower.
[0040] Next, the solid obtained by evaporation to dryness is calcined. In the calcination, it is preferable to remove carbon contained in the solid by adjusting the calcination temperature. For this purpose, the calcination temperature is preferably 700°C or more and 1000°C or less, more preferably 750°C or more and 950°C or less, and even more preferably 800°C or more and 900°C or less. The calcination time is preferably from 1 hour to 10 hours, more preferably from 3 hours to 7 hours, and even more preferably from 4 hours to 6 hours. The calcination atmosphere is not particularly limited, and in industrial practice, it is convenient to use air.
[0041] The calcined product thus obtained is pulverized to obtain a powder having an adjusted particle size, and then the powder is molded into a predetermined shape, preferably by a combination of, for example, a uniaxial press using a hydraulic press and a cold isostatic press.
[0042] The compact thus obtained is fired to obtain a sintered body made of a composite oxide having a desired composition. The firing temperature is preferably from 1000° C. to 1500° C., more preferably from 1200° C. to 1450° C., and even more preferably from 1250° C. to 1400° C. The firing time is preferably from 1 hour to 20 hours, more preferably from 3 hours to 15 hours, and even more preferably from 5 hours to 10 hours. The firing atmosphere is not particularly limited, and in industrial practice, it is convenient to use air atmosphere.
[0043] The composite oxide thus obtained is preferably an n-type mixed conductor having electronic conductivity and oxide ion conductivity. Taking advantage of this advantage, the composite oxide can be used as an electrode of an electrochemical cell. When the composite oxide of the present invention is used as an electrode of an electrochemical cell, the reduction reaction of oxygen on the electrode surface, which is the rate-limiting step, can be promoted. As a result, the composite oxide of the present invention exhibits high electrode activity even in the medium and low temperature range. Therefore, the composite oxide of the present invention is useful as a constituent material of electrochemical elements utilizing oxide ion conductivity, such as oxygen sensors, solid electrolyte fuel cells, and oxygen permeation elements. EXAMPLES
[0044] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to such examples. Unless otherwise specified, "%" means "% by mass".
[0045] [Examples 1 to 3] Ca(NO3)2·4H2O was used as the A element source, Mn(NO3)2·6H2O was used as the B element source, and Co(NO3)2·6H2O was used as the C element source. A solution was prepared by adding 3 moles of citric acid and 3 moles of propylene glycol to 1 mole of Ca(NO3)2·4H2O. Mn(NO3)2·6H2O was dissolved in pure water to prepare a 1 mol / L aqueous solution. A solution was prepared by adding 3 moles of citric acid and 3 moles of propylene glycol to 1 mole of Co(NO3)2·6H2O. These solutions were mixed so as to obtain the molar ratios of calcium, manganese and cobalt shown in Table 1 below.
[0046] The mixed solution was heated to 150°C in an air atmosphere to cause an esterification reaction. It was further heated to 300°C to evaporate and dry to obtain a solid. It was then heated in an electric furnace at 400°C for 2 hours for carbonization. This solid was heated to 900°C in an air atmosphere to obtain a calcined product. The calcined product was pulverized using a ball mill to obtain a powder. The powder was uniaxially pressed at 50 MPa for 3 minutes using a hydraulic machine to obtain a provisional compact. The provisional compact was cold isostatically pressed at 200 MPa for 1 minute to obtain a final compact. The final compact was fired at 1250°C in an air atmosphere for 10 hours to obtain the desired sintered composite oxide.
[0047] For the composite oxide of Example 2, the average valences of Mn and Co were measured by high-resolution X-ray fluorescence analysis. The composite oxide powder and cellulose powder were mixed, and the mixed powder was pressure molded using an aluminum ring (inner diameter 35 mmφ) to prepare a measurement sample. The measuring device used was Xspecia (registered trademark, manufactured by Shimadzu Corporation), and the peak energy (eV) of the Mn Kβ1 line and Co Kα1 line spectrum obtained by irradiating the sample with X-rays was obtained. The calibration curve for Mn valence analysis was created from the energy of the Kβ1 line of LiMn2O4 (Mn3.5 valence) and Li2MnO3 (Mn4.0 valence). The calibration curve for Co valence analysis was created from the energy of the Kα1 line of CoO (Co2.0 valence) and LiCoO2 (Co3.0 valence). The average valence of Mn and Co in the sample calculated using these calibration curves was 3.8 for Mn and 2.8 for Co.
[0048] Comparative Example 1 In this comparative example, Ba was synthesized according to the method described in Non-Patent Document 1 (Chem. Mater. 2019, 31, 2713-2722). 0.9 Nd 0.1 In 0.7 Mn 0.3 O 3-δ (hereinafter referred to as "BNIM"). Ba(NO3)2 was used as the barium source, Nd(NO3)3·6H2O was used as the neodymium source, In(NO3)3·xH2O was used as the indium source, and Mn(NO3)2·6H2O was used as the manganese source. These nitrates were dissolved in distilled water, and 6 moles of citric acid and 6 moles of propylene glycol were added per mole of the nitrates. The solution thus obtained was heated to 150°C, and then heated to 400°C in an air atmosphere to evaporate and dry to obtain a solid. This solid was heated to 900°C in an air atmosphere to obtain a calcined product. The calcined product was pulverized in a ball mill to obtain a powder. The powder was formed into pellets, and the molded product was fired at 1400°C for 5 hours in an air atmosphere to obtain a sintered BNIM. The valence of neodymium in the obtained BNIM was trivalent, unchanged from the raw material Nd(NO3)3·6H2O.
[0049] [Rating 1] X-ray diffraction measurements were performed on the composite oxides obtained in the examples to determine the crystal structure and lattice constant, and further calculate the lattice volume. The results are shown in Fig. 1 and Table 1. As is clear from the results shown in Fig. 1, the composite oxides obtained in Examples 1 and 2 were single phases with an orthorhombic perovskite-type structure indicated by ●. In the composite oxide obtained in Example 3, in addition to the main phase with an orthorhombic perovskite-type structure, a secondary phase of Ca3CoMnO6 indicated by △ and a secondary phase of CaO indicated by □ were also observed.
[0050] 〔Evaluation 2〕 The temperature dependence of the Seebeck coefficient of the composite oxides obtained in Examples 1 to 3 was measured by the following method. The results are shown in Fig. 2. As is clear from the results shown in the figure, it can be seen that the composite oxides obtained in each example have a negative Seebeck coefficient at temperatures from 300 °C to 900 °C.
[0051] <Seebeck coefficient> The sintered bodies of the composite oxides obtained in the examples and comparative examples were cut into rectangular parallelepipeds with a length of about 13 mm × width of 2.9 mm × thickness of 2.1 mm. Platinum electrodes were provided at both ends of this rectangular parallelepiped sample, and a nichrome wire was attached to one side of the platinum electrode. This sample was placed in an electric furnace open to the atmosphere and heated from 300 °C to 900 °C. The nichrome wire was heated to generate a temperature gradient in the sample, and the Seebeck (Seebeck) coefficient was calculated using Equation (4) from the temperature difference measured at both ends of the sample and the value when the thermoelectromotive force was maximized.
[0052]
Equation
[0053] 〔Evaluation 3〕 The oxide ion conductivity at 800 °C and the total electrical conductivity at 800 °C of the sintered bodies of the composite oxides obtained in the examples and comparative examples were measured by the following method. The results are shown in Table 1.
[0054] <Oxide ion conductivity> Oxide ion conductivity σion is the oxygen flux value j O2 The sintered bodies of the composite oxides obtained in the examples and comparative examples were polished to a thickness of 1 mm, and the sintered bodies were sandwiched between two glass tubes, sealed with glass, and heated to 800°C in an electric furnace. Air was circulated through one of the glass tubes, and helium was circulated through the other. The gas composition on the helium flow side was analyzed by gas chromatography, and the oxygen permeation flux j O2 was calculated using equation (5).
[0055]
number
[0056] In the formula, Q He is the flow rate of helium (sccm), S is the area of the sintered body in contact with the gas (cm 2 [O2]perm (ppm) is the net concentration of oxygen that has permeated, and is the value obtained by subtracting 1 / 4 of the nitrogen concentration [N2] (ppm), which corresponds to the mechanical air leak, from the measured oxygen concentration on the permeation side. Oxygen ion conduction σ ion was calculated using the following formula (6).
[0057]
number
[0058] In the formula, R is the gas constant, T is the temperature (K), F is the Faraday constant, P′O2 and P″O2 are the oxygen partial pressures on the air side and the permeation side, respectively, and L is the thickness of the sintered body (cm).
[0059] <Total electrical conductivity> The temperature dependence of the total electrical conductivity was evaluated by the direct current two-terminal method. The rectangular specimens used for the Seebeck coefficient measurements were used for the measurements. Measurements were performed in the range of 300°C to 900°C using a tube furnace. The total electrical conductivity was calculated from the electrical resistance at each temperature.
[0060] [Rating 4] The oxygen surface exchange reaction rates at 600° C. of the composite oxides obtained in the Examples and Comparative Examples were measured by the following method. The results are shown in Table 1. The oxygen surface exchange reaction rate was evaluated by the pulse isotope substitution method. 18 This is a method to estimate the rate of oxygen surface exchange reactions by tracking O. 16 O 16 O( 32 The powder of the composite oxide is heat-treated in a state where a carrier gas containing O2 is circulating, and the isotope oxygen is added to it. 18 O 18 O( 36 A gas containing O2 was injected for just a moment. 18 O 18 O( 36 O2) in the sample 16 O. The amount of exchange depends on the electrochemical activity of the sample, which makes it possible to calculate the oxygen surface exchange reaction rate. Specifically, the composite oxides obtained in the examples and comparative examples were pulverized into powder. 30 mg to 50 mg of the pulverized powder was used and filled into a quartz tube with an inner diameter of 3 mm so that the powder was sandwiched between glass wool from above and below. This quartz tube was attached to a vertical furnace. Next, a carrier gas (10% 32 O2-N2) was passed at 50sccm, and mixed gas containing isotope oxygen (10% 36 O2-He) was introduced in a pulsed manner using an automatic gas sampler (GL Science Inc.; GS-5000A). 18 O 18 O( 36 O2), 16 O 18 O( 34 O2), 16 O 16 O( 32 The oxygen surface exchange reaction rate R0 was determined by measuring the ratio of oxygen moles in the gas phase n, the average gas residence time τ, and the specific surface area S of the powder sample. w , Entrance side 18 O fraction f in 18 , exit side 18 O fraction f ex18 Using this, it is expressed by the following equation (7).
[0061]
number
[0062] In the formula, R0 is the molar amount of oxygen per unit area and unit time. S w is the specific surface area of the sample, measured by nitrogen adsorption method and calculated by the BET method. 18 is calculated using the following equation (8).
[0063]
number
[0064] In the formula, f 36 teeth 18 O 18 O( 36 O2) fraction, f 34 teeth 16 O 18 O( 34 O2) fraction.
[0065] [Table 1]
[0066] As is clear from the results shown in Table 1, the composite oxides obtained in the examples have higher oxide ion conductivity and total electrical conductivity than the composite oxides of the comparative examples. It is also apparent that the composite oxides obtained in the Examples have a higher oxygen surface exchange reaction rate than the composite oxides of the Comparative Examples.
Claims
1. A complex oxide represented by the following formula (1), having a lattice volume of 207 Å 3 or more and 210 Å 3 or less, and having a perovskite structure having oxygen vacancies. A x B y C 1.00-y O z (1) In formula (1), A is Ca, B is Mn, and C is Co; x represents a number of 0.95 or more and 1.05 or less, y represents a number of 0.65 or more and 0.95 or less, z represents a number of 2.3 or more and 3.1 or less.
2. Lattice volume is 207.5 Å 3 More than 209.0 Å 3 2. The composite oxide according to claim 1, wherein:
3. 3. The composite oxide according to claim 1, which is an n-type mixed conductor having conductivity through electrons and oxide ions.
4. 4. The composite oxide according to claim 1, which has a negative Seebeck coefficient at a temperature of 300° C. or higher and 900° C. or lower.
5. 5.0×10 at 800° C. -4 5. The composite oxide according to claim 1, having an oxide ion conductivity of 1.5 S / cm or more.
6. 6. The composite oxide according to claim 1, having a total electrical conductivity of 5.0 S / cm or more at 800°C.
7. The oxygen surface exchange reaction rate at 600°C is 1.0 x 10 -5 mol / m 2 The composite oxide according to claim 1 , wherein the molecular weight is 1 / s or more.
8. An electrochemical device comprising the composite oxide according to claim 1 .
Citation Information
Patent Citations
High temperature conductive oxide, electrode for fuel cell and fuel cell using the same
JP2002097021A
Composite oxide having n-type thermoelectric characteristic
JP2005051103A
Mixed ionic and electronic conductive membranes
JP2009509751A
Composition for thermoelectric element
JP2013168451A
Perovskite related compound
JP2015063438A